Pengaruh Model PjBL Berbantuan Media Interaktif Terhadap Kemampuan Berpikir Kritis Siswa Kelas III SD - Utami, Erina Mumpuni Tri; Sari, Yunita (Didaktika, 2025)
Critical thinking ability is a skill that helps students understand concepts, solve problems, and make decisions in learning. Students' low critical thinking skills are a concern because they can affect learning outcomes in all subjects. This research aims to determine the effect of the Project-Based Learning (PjBL) model assisted by interactive media on the critical thinking abilities of third-grade elementary school students. The method used is a quantitative method with an approach of pre-experimental design which focuses on one experimental class. The type of research applied is one group pretest-posttest at Sultan Agung Islamic Elementary School 4. Data collection techniques include initial observation, interviews, and research using pre-test, treatment, and post-test. Data analysis techniques include testing validity, reliability, distinguishing power, and level of difficulty, as well as going through initial and final data analysis stages. The results of this research show that the PjBL model assisted by interactive media has an effect on the critical thinking abilities of third-grade elementary school students. This is proven by the Sig value. (2-tailed) on the results of hypothesis testing paired sample t-test namely 0.000 0.05, so H0 rejected and Ha accepted. Practically, this research is useful for teachers because the PjBL model assisted by interactive media can be applied as an innovative learning strategy to improve students' critical thinking skills, especially in science and science subjects. Theoretically, this research supports the theory that project-based learning can increase students' active involvement, which ultimately helps students to develop their critical thinking abilities.